Phenomics for Abiotic Stress Tolerance - Challenges Ahead - Maiti, Ratikanta; Satya, Pratik (International Journal of Bio-resource and Stress Management, 2023)
In the next fifty years, planet earth is going to have a burden of 8-10 billion of human population, 25-50% more degraded land, additional 48.6% CO2 in atmosphere and a temperature increase by at least 2oC (Jaggard et al., 2010). The impact of such dramatic changes on plant ecology and crop cultivation system projects a frightening scenario in the next fifty to hundred years. A United Nations report has estimated that the climatic changes together can cause a fall in food production by 25%, resulting in more hunger, increased price of food and increasing possibilities of war over food. With a current rate of 10 ha minute-1 soil degradation and 23 ha minute-1 deforestation at global level as stated in UNCCD Secretariat Recommendations for Policymakers published in April, 2012